Culex quinquefasciatus: status as a threat to island avifauna and options for genetic control - Tim Harvey-Samuel; Thomas Ant; Jolene Sutton; Chris N. Niebuhr; Samoa Asigau; Patricia Parker; Steven Sinkins; Luke Alphey (CABI Agriculture and Bioscience)
Abstract The avifauna endemic to islands is particularly susceptible to population declines and extinctions resulting from the introduction of non-native pathogens. Three pathogens of concern are the avian malaria parasites, the avian poxviruses, and West Nile virus—each of which can be transmitted by Culex quinquefasciatus, a highly adaptive and invasive mosquito. Culex quinquefasciatus has dramatically expanded its range in recent centuries and is now established throughout much of the tropics and sub-tropics, including on many islands that are remote from mainland landmasses and where this geographic separation historically protected island species from mosquito-borne diseases. The potential for ecological disruption by Cx. quinquefasciatus has been particularly striking in the Hawaiian Islands, where the introduction and transmission of avian malaria and avian poxvirus led to the extinction of several endemic bird species, with many more at risk. With Cx. quinquefasciatus now present in many insular communities and global trade and tourism increasing links between these areas, both to each other and to mainlands, there is growing concern that patterns of avian decline in Hawai‘i may be played out in other insular ecosystems. The implementation of traditional methods for Cx. quinquefasciatus control, including larval source management, is often impractical at large scale and when breeding sites are numerous and difficult to locate—typical issues associated with invasive species removal. One alternative approach would be the utilisation of genetic control methods, several of which have been successfully developed in other mosquitos such as Aedes aegypti and the malaria vector Anopheles gambiae. However, the development of similar tools for Cx. quinquefasciatus has been comparatively limited. Here we review the threat that Cx. quinquefasciatus poses as a vector of avian pathogens to island avifauna and discuss specific examples of at-risk bird populations on the islands of Hawai‘i, New Zealand and Galápagos. We also review the major options for the deployment of genetic control tools against Cx. quinquefasciatus, and discuss the current state of the field with a focus on radiation-based sterilisation, transgenic methods, and transinfections using the bacterial endosymbiont Wolbachia.